A relação entre filosofia da linguagem e as penas negociadas - Pinto, Luís Frederico Balsalobre (2021)
This thesis intends to investigate the relationship between philosophy of language and the plea bargaining. For this, we investigated the relationship between philosophy and Criminal Law in history, analyzing the nexus between classical philosophy and the system of punishment in ancient and primitive peoples, modern philosophy and the judicial system of punishment and the philosophy of language, in comparison with the plea bargaining. After the historical research with philosophy influenced each phase of Criminal Law, we started to analyze how the overcoming of metaphysics, by the philosophy of language, influences the modern dogmatic of Criminal Law. In the last chapter, we expound on the genealogy of the plea bargaining in the United States of America and Europe, looking at some existing philosophical basis. From this genealogical analysis of the penal negotiation system, we can conclude whether there is a relationship, and how the philosophy of language can contribute to the creation of a specific dogmatic to the plea bargaining which, if it is not a complete novelty in Brazil, was expanded by recent legislation, urgent the delimitation of dogmatic standards, as much as modern dogmatic is already delimited